Permodelan pelaksanaan teknologi hijau dalam pengurusan di agensi kerajaan - Ismaniza, Ishak (2021)
This study is about the implementation of green technology modelling in transportation management in government agencies, It was conducted at the Royal Malaysian Police Department. This study examined the weakness of the existing model and made improvements on the model, This study employed a qualitative approach, phenomenography method, direct interviews, open- ended questions and purposive sampling, It also uses in-depth interview instruments, Transport has been identified as the primary source of carbon emission that is the second highest in Malaysia at 21 per cent. In addition, the Royal Malaysia Police was the department that used vehicles the most compared to other government departments. This research studied the transportation used by the Royal Malaysian Police. The existing model used by the Royal Malaysian Police states what can be achieved but does not state clearly how that goal can be achieved effectively, Research on the model is limited due to the lack of research in the implementation of green technology in transportation management in government agencies, This was seen through the article search in almost all green technology journals related to transportation management in government agencies, Objective of the study is to identify the implementation of green technology practices and achievement of the implementation of green technology in transport management. It also intended to identify the factors that led to the constraints of green technology implementation in transport management, develop institutional model in the implementation of green technology in transportation management at government agencies, and test and evaluate the model. This study contributes to green practices and green technology applications that can produce new ideas from theoretical and practical aspects, Finally, this study has also developed a new, relevant, practical and comprehensive model of the existing model that contributes to the organization.